Design of self-tuneable mass damper for modular fixturing systems. Issue 1 (2016) - Munoa, Jokin; Iglesias, Alex; Olarra, Aitor; Dombovari, Zoltan; Zatarain, Mikel; Stepan, Gabor
Abstract: Enhancing dynamic characteristics of fixtures for large workpieces is essential to assure chatter free machining of heavy-duty milling operations. Variable stiffness tuned mass dampers (VSTMD) can effectively improve the dynamic stiffness of modular fixtures by changing their dynamic characteristics. The theory of a new VSTMD concept is presented. Their realisable optimal tuning is determined and the results are compared to the standard constant stiffness TMDs. By means of the developed automatic tuning procedure, stiffness is varied via a rotary spring, while damping is provided by eddy currents. The prototype and the effectiveness of the concept are experimentally validated by heavy-duty milling tests on a modular fixture.